Soybean genetic diversity in time and among breeding programs in Brazil - Priolli, Regina Helena Geribello; Mendes-Junior, Celso Teixeira; Sousa, Sandra Mara Bispo; Sousa, Neylson Eustáquio Arantes; Contel, Eucleia Primo Betioli (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to detect the effects of plant breeding over the genetic diversity of soybean germplasm grown during the last three decades by comparing six different breeding programs and releasing intervals of soybean cultivars, using microsatellite loci. Regarding the breeding programs, all loci presented significantly different allelic distributions. Some loci presented alleles restricted to unique breeding programs, while others had a same allele being the most frequent in all the six programs. The AMOVA revealed that the major proportion of the variance occurred among cultivars within breeding programs and only 5.3 (p<0.05) of the whole variance was due to differences among breeding programs. When the breeding programs were pairwise-compared, five out of the 15 comparisons showed significant differences (p<0.05), being the IAC program within four of them. Soybean variability estimates of the five different releasing intervals revealed that just 1.78% of the variance is due to differences among them (p>0.05). The results suggest that the soybean germplasm pool involved in breeding programs in Brazil has maintained a stable genetic diversity during the past 30 years, in addition to a relative heterogeneity of some breeding programs.